Louis Lamm (1871-1943): A Short Biography of a Dedicated Judaica Publisher and Bookseller. - Freudenthal, Gad (Zutot: Perspectives on Jewish Culture, 2017)
Louis Lamm was a famed bookseller and publisher of Judaica in Berlin and Amsterdam during the four decades preceding his assassination in 1943. Yet even Internet fails to provide elementary biographical details about his life and work. The aim of this short paper is to partially fill this lacuna and contribute to the perpetuation of the memory of a dedicated lover of Jewish books